STRES KERJA, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SAPTA SENTOSA JAYA ABADI DI KAB. MUKOMUKO - Rizki Digo Saputra; Febsri Susanti (LP2M Universitas Bina Bangsa, 2024)
This research aims to examine the influence of work stress, workload and work environment on employee performance at PT. Sapta Sentosa Jaya Abadi in Kab. Mukomuko. This type of research is quantitative, where this research uses numerical data and the research process emphasizes measuring objective results using statistical analysis. Data were collected through distributing questionnaires to 107 respondents using saturated sampling techniques, where all members of the population were sampled, using instrument tests (validity tests and reliability tests), descriptive analysis, classical assumption tests (normality tests, multicollinearity tests and heteroscedasticity tests) multiple linear regression and t test, with the help of the SPSS application. The results of the research show that work stress has a positive and significant effect on employee performance at PT. Sapta Sentosa Jaya Abadi in Kab. Mukomuko, workload has a positive and significant effect on employee performance at PT. Sapta Sentosa Jaya Abadi in Kab. Mukomuko, and the work environment have a positive and significant effect on employee performance at PT. Sapta Sentosa Jaya Abadi in Kab. Mukomuko. Which means the first hypothesis is accepted, the second hypothesis is accepted and the third hypothesis is accepted